UJARAN KEBENCIAN DALAM PERSPEKTIF AGAMA ISLAM DAN AGAMA BUDDHA - Muhammadin Muhammadin; Murtiningsih Murtiningsih; Septi Yana (Fakultas Ushuluddin dan Pemikiran Islam Universitas Islam Negeri Raden Fatah Palembang, 2019)
Religion was born as a response to human life which deviated from the nature of humanity, as well as Islam and Buddhism. Speech of hatred is an act that deviates from the teachings of religion. Speech of hatred according to Islam is despicable morality (akhlak madzmumah) which is contrary to the commands of Allah SWT, because the utterances of hatred are bad words or sayings in which consists hurting factor to the others. While the utterances of hatred according to Buddhism are included in the false speech which violates the 4th precept, namely musavvada veramani sikkhapada samadiyami and violates the rules of Buddhist morality. Speech of hatred is forbidden in Islam and Buddhism because it will cause the culprit to go to hell. Islam emphasizes the prohibition of utterance of hatred compared to Buddhism because it is clearly punished by Allah SWT and consider to be big sin while in Buddhism it is not to be really emphasized because in Buddhism legal karma is better known.